Introduction to the JPCC special issue: Professionalism in the Pandemic. Issue 3 (28th July 2020) - Scanlan, Martin
Abstract : Purpose: Introduction to the JPCC special issue: Professionalism in the Pandemic . Design/methodology/approach: As educators around the world respond to the global COVID-19 pandemic, the Journal of Professional Capital and Community (JPCC), the International Congress for School Effectiveness and Improvement (ICSEI) and the ARC Education Project are collaboratively launching a special issue of JPCC: Professionalism in the Pandemic . This essay provides a brief introduction to this special issue. Findings: The purpose of this special issue is to create a scholarly forum for sharing perspectives from around the world about how educators in classrooms, schools, school systems and broader communities are innovatively, creatively and productively responding to this unfolding crisis. Some guiding questions these essays consider: In your field/area of expertise, what are some examples of creative responses to the pandemic that you are witnessing? What lessons do you see educators learning in the short term? Medium term? Long term? What are some ways the current crisis is spurring new opportunities to build professional capital and community? How are educators (re)conceptualizing their roles in the face of this crisis? What kinds of connections are educators fostering to support one another through this time? How are responses exhibiting consistency and variation internationally? Originality/value: The thought leaders contributing to this special issue come from around the world. Speaking in the voice of public intellectuals, they provide perspectives for practitioners and policymakers who are seeking to not simply adapt to meet the crisis at hand but also to step back and consider the medium to longer-term implications.